The role of iron metabolism indicators in predicting gestational diabetes mellitus - A. O. Torosyan; E. V. Loginova; C. G. Gagaev (Сахарный диабет)
Iron (Fe) deficiency and hyperglycaemia are both widely found throughout the world among pregnant women. According to the latest data from the American Diabetes Association (ADA), the prevalence of gestational diabetes mellitus (GDM) has increased and reaches 15–20%. Nowadays, there is growing evidence that a link between Fe metabolism and glucose homeostasis exists. The study of changes in the indicators of Fe metabolism in the serum of pregnant women with glucose intolerance and GDM plays an important role in expanding the understanding of the pathogenesis of these conditions. The hypothesis that excess Fe increases the risk of developing GDM has prompted us to review and evaluate the potential relationship between elevated Fe levels and the risk of developing GDM. The aim is to integrate all available data on the correlation between GDM and Fe status in the body. It is increasingly being recognised that excess Fe accumulation in the body is associated with an increased risk of diabetes. There is no available data on the relationship between serum ferritin and GDM in the Russian population, while early identification of the risk of GDM development will be of great importance for its related health effects and prevention. The role of Fe status as a GDM biomarker in high-risk populations is of interest, both for prognostic and diagnostic measures, and for therapeutic interventions. For a better understanding of whether an excess of Fe increases the risk of developing GDM, studies are needed to reveal the role of Fe in the mechanisms of GDM development.